Directions for Land Conservation Based on Determining the Erosion Hazard Index (EHI) Using the RUSLE Method in Sub-Watersheds Gunting, Jombang - Novita, Dian; Wijaya, Kemal; Sasongko, Purnomo Edi (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2024)
Land damage generally occurs due to erosion by the flow of rainwater on the soil surface. Erosion is closely related to the intensity of rainfall in an area and the slope of the land (slope). Soil erosion is an environmental problem which, if left unchecked in the long term, can reduce soil fertility. The Erosion Hazard Index (EHI) is used as a solution in controlling erosion at certain locations. The research was conducted in the Kali Gunting Sub-watershed in Wonosalam District, Jombang, East Java, in January 2021 to April 2023. The research locations covered several villages, namely: Galengdowo, Jarak, Wonomerto, Sambirejo, Wonosalam, Carangwulung, Panglungan, Wonokerto and Sumberrejo. Meanwhile, for soil sample analysis activities carried out at the Land Resources Laboratory I and II of the Faculty of Agriculture, East Java "Veteran" National Development University. Determination of the Erosion Hazard Index (EHI) is conductedusing the RUSLE method. The results showed that the villages of Carawangwulung, Jarak, Wonokerto, Sumberejo, Wonosalam, Wonomerto, Galengdowo, Sambirejo and Panglungan had EHI in the very low category. Efforts that can be made to maintain the rate of erosion are to maintain annual plants, add organic mulch from the remaining twigs and leaves, change traditional terraces to bench terraces and apply the Groundwater Conservation Area system. Furthermore, land with traditional terrace conservation in Sambirejo and Wonokerto sub-districts can be replaced by making bench terraces.